2013
DOI: 10.1029/2012jd018136
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and black carbon aerosols in the Los Angeles Basin during CalNex

Abstract: [1] We evaluate predictions from the Community Multiscale Air Quality (CMAQ version 4.7.1) model against a suite of airborne and ground-based meteorological measurements, gas-and aerosol-phase inorganic measurements, and black carbon (BC) measurements over Southern California during the CalNex field campaign in May/June 2010. Groundbased measurements are from the CalNex Pasadena ground site, and airborne measurements took place onboard the Center for Interdisciplinary Remotely-Piloted Aircraft Studies (CIRPAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 147 publications
(123 reference statements)
1
8
0
Order By: Relevance
“…The data have been averaged into 0.5° longitude bins to better quantify the trend in oxidation from west to east. Four‐hour and 12h back trajectory analysis confirms that the air sampled in the El Cajon and Banning passes originated primarily in the basin [ Metcalf et al , ; Ensberg et al , ]. The data downwind of Banning Pass and east of longitude −116.5 exhibited influence from southernly air masses and not from the Banning Pass.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The data have been averaged into 0.5° longitude bins to better quantify the trend in oxidation from west to east. Four‐hour and 12h back trajectory analysis confirms that the air sampled in the El Cajon and Banning passes originated primarily in the basin [ Metcalf et al , ; Ensberg et al , ]. The data downwind of Banning Pass and east of longitude −116.5 exhibited influence from southernly air masses and not from the Banning Pass.…”
Section: Resultsmentioning
confidence: 70%
“…The atomic O:C ratio of the OA (Figure , shown as the marker color) for 19, 21, and 25 May is relatively high in the southwestern basin, near Long Beach. Back trajectory analysis shows that the oxidized aerosol mass in this region of the basin originates from an aged air mass that was transported up the coast [ Ensberg et al , ]. The relatively high O:C in this region was not observed on 28 May.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on sources and composition of aerosol particles in both SJV (Ahlm et al, ; Young et al, ; Zhang et al, ) and SoCAB (Chan et al, ; Craven et al, ; Hayes et al, ; Hersey et al, ) have mostly been limited to bulk PM 2.5 or PM 1 measurements. Only a few studies have reported high‐resolution size‐resolved compositions of aerosol particles with on‐line time resolution in these regions (Ensberg et al, ; Ge, Setyan, et al, ; Ge, Zhang, et al, ; Liu et al, ; Ying & Kleeman, ). Ge, Setyan, et al () estimated average daily mass size distributions of organic aerosols (HOA, BBOA, COA, and OOA) in Fresno using multilinear analysis of the size‐resolved mass spectra.…”
Section: Introductionmentioning
confidence: 99%
“…These evaluations are especially important for fine‐scale simulations of secondary pollutants such as NH 4 + and NO 3 − in complex environments such as SoCAB and SJV that resolve detailed air pollution processes under challenging conditions. Fine‐scale modeling (i.e., 4 km horizontal resolution) is currently used for air quality management in California [ SCAQMD , ; SJVAPCD , ] and in research studies focused on California [e.g., Angevine et al , ; Baker et al , ; Ensberg et al , ; Fast et al , ; Kelly et al , ; Ying, ], while national‐scale assessments use coarser resolution (generally 12 to 50 km) for computational efficiency [ Schiferl et al , ; Huang et al , ; U.S. EPA , ; Walker et al , ; Heald et al , ].…”
Section: Introductionmentioning
confidence: 99%